Pengaruh Sektor Pariwisata dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Provinsi Bali - Mohammad Wasil; Dina Fitria Sari (Universitas Negeri Surabaya, 2025)
Abstract This study examines how the amount of visitors, lodging options, tourism attractions, and local taxes affect Bali Province's local income between 2014 and 2024. The findings, which are based on panel data and a fixed effect model (FEM), indicate that municipal taxes and tourist attractions have a considerable positive impact on local revenue, whereas the quantity of visitors and hotel accommodations have a positive but negligible impact. These results show that efficient administration of tourist attractions and local taxes has a greater impact on a rise in local revenue.